Get to know Mac OS X Leopard - Ablan, Dan.; Safari eBooks ([United States] : Peachpit Press, 2010)
"This 2-1/2 hour training video gets you up to speed quickly on your Mac. You'll learn to navigate the interface and work with the Finder, Folders, and Desktop. Once you have the basics down, you'll set up email and enter contacts, use Time Machine, explore iLife applications, and much much more. Numerous tips and tricks throughout makes learning the Mac OS a breeze"--Resource description page (viewed Jan. 11, 2011).
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title from resource description page (viewed Jan. 11, 2011).
Presenter, Dan Ablan.
Keywords: Operating systems (Computers); Mac OS; Electronic books